Lipid nanoparticles with accessible nickel as a vaccine delivery system for single and multiple his-tagged HIV antigens - Yan, Weili (Dove Medical Press, 2009)
Lipid-based nanoparticles (NPs) with a small amount of surface-chelated nickel (Ni-NPs) were developed to easily formulate the human immunodeficiency virus (HIV) his-tagged Tat (his-Tat) protein, as well as to formulate and co-deliver two HIV antigens (his-p24 and his-Nef) on one particle. Female BALB/c mice were immunized by subcutaneous injection with his-Tat/Ni-NP formulation (1.5 μg his-Tat/mouse) and control formulations on day 0 and 14. The day 28 anti-Tat specific immunoglobulin G titer with his-Tat/Ni-NPs was significantly greater than that with Alum/his-Tat. Furthermore, splenocytes from his-Tat/Ni-NP-immunized mice secreted significantly higher IFN-γ than those from mice immunized with Alum/his-Tat. Although Ni-NPs did not show better adjuvant activity than Tat-coated anionic NPs made with sodium dodecyl sulfate (SDS/NPs), they were less toxic than SDS/NPs. The initial results indicated that co-immunization of mice using his-p24/his-Nef/Ni-NP induced greater antibody response compared to using Alum/his-p24/his-Nef. Co-delivery of two antigens using Ni-NPs also increased the immunogenicity of individual antigens compared to delivery of a single antigen by Ni-NPs. In conclusion, Ni-NPs are an efficient delivery system for HIV vaccines including both single antigen delivery and multiple antigen co-delivery.